Yield of Lumbar Puncture with First Complex Febrile Seizure - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers in emergency medicine and pediatric neurology at Children's Hospital Boston, MA, assessed the rate of acute bacterial meningitis (ABM) among 526 children (56% male) aged 6 to 60 months (median age 17 months) who were evaluated in the ED between 1995 and 2008 for a first complex febrile seizure (CFS).